What Are the Stages of the Creative Process? What Visual Art Students Are Saying. - Botella, Marion (Front Psychol, 2018)
Within the literature on creativity in the arts, some authors have focused on the description of the artistic process (Patrick, 1937; Getzels and Csikszentmihalyi, 1976; Mace and Ward, 2002; Yokochi and Okada, 2005) whereas others have focused on the creative process (Wallas, 1926; Osborn, 1953/1963; Runco and Dow, 1999; Howard et al., 2008). These two types of processes may be, however, somewhat distinct from each other because the creative process is not always dedicated to artistic creation, and productive work in the arts may not always involve creativity, in terms of specifically original thinking. Our goal is to identify the specific nature of the artistic creative process, to determine what are the basic stages of this kind of process. This description can then be integrated in a Creative process Report Diary (CRD; Botella et al., 2017) which allows self-observations in situ when participants are creating.